The Royal Air Force in Texas : training British pilots in Terrell during World War II - Killebrew, Tom (War and the Southwest series, 2003)
With the outbreak of World War II, British RAF officials sought to train aircrews outside of England, safe from enemy attack and poor weather. In the USA, six civilian flight schools dedicated themselves to instructing RAF pilots. Tom Killebrew explores the history of the Terrell Aviation School.